ANALISIS SIFAT TERMIS BIJI KEDELAI SEBAGAI ACUAN RANCANG BANGUN ALAT PENGERING THERMAL PROPERTIES ANALYSIS OF SOYBEAN AS A REFERENCE OF DRYER DESIGN - , Siswantoro (Pembangunan Pedesaan, 2005)
The objectives of this research were to give information about the characteristic of thermal conductivity (k), thermal diffusivity (a), and specific heat (Cp) of soybean grain due to the influence of moisture content and bulk density. This research was conducted in laboratory and was carried out at various moisture contents of 11 to 20 percent wet basis and bulk density from 850 to 900 kg/mÂ³. The instrument used was PVC cylinder with 10 cm diameter and 25 cm length. At the central point along the cylinder was stretched a neckline heating wire as a line heat source supplied by a direct current (DC) electric. In order to get timetemperature data for calculating value of k, a, and Cp of soybean grain, instrument for measuring temperature were placed at two locations: first at the distance < 2.8 mm and second between 11.9 to 17.3 mm from center cylinder. Result of the experiment consisted of k in W/m. C, a in mÂ²/sec., and Cp in J/kg. C described as following empirical equation: k = 3,037 x 10-1 + 3,924 x 10 -3 ka + 4,604 x 10-4 Ï Î±= 4,051 x 10-7 + 0,909 x 10-8 ka + 4,709 x 10 -10 Ï Cp = 4,478 x 103 4,722 x 10-1 ka 2,807 Ï Value thermal conductivity and diffusivity of soybean grain in bulk increase linearly due to the increasing moisture content and bulk density, but value of specific heat decreases linearly due to the increasing moisture content and bulk density. Implication of the experiment result is that standard moisture content and bulk density are needed for giving information of thermal properties value, especially for soybean grain.